TMPRSS2 Correlated With Immune Infiltration Serves as a Prognostic Biomarker in Prostatic Adenocarcinoma: Implication for the COVID-2019 - Luo, Lianxiang; Zheng, Yushi; Li, Mingyue; Lin, Xinjie; Li, Xiaodi; Li, Xiaoling; Cui, Liao; Luo, Hui (Frontiers in Genetics, 2020)
Type 2 transmembrane serine protease (TMPRSS2) is a new member of the serine proteases, and studies have shown that TMPRSS2 plays a role in the occurrence of prostate malignancies and is closely related to the occurrence of the coronavirus disease 2019 (COVID-19). However, the role of TMPRSS2 in prostatic adenocarcinoma (PRAD) remains largely unclear. To better explore its function in PRAD, we examined the expression level of TMPRSS2 in the GEO, TIMER as well as Oncomine databases and studied the association between TMPRSS2 and overall survival rates in the UALCAN and GEPIA databases. In addition, we studied the correlation of the level of immune infiltration and markers of immune cell type in the TIMER database, analyzed the prognosis based on the expression level of TMPRSS2 in the related immune cell subsets, and determined the methylation profile of TMPRSS2 promoter by UALCAN database. Subsequently, we conducted a survival analysis and GO pathway analysis in the TISID database and detected the expression of TMPRSS2 in the HPA database. We also studied the PPI network of TMPRSS2 in the GENEMANIA database. Additionally, we used the microarray GSE56677 and GSE52920 to illustrate changes in TMPRSS2 expression in vivo and in vitro after SARS-COV infection, finding that expression of TMPRSS2 decreased after SARS-COV infection in vitro. The function of TMPRSS2 in the dataset was further verified by GSEA analysis. In conclusion, the expression of TMPRSS2 is significantly increased in PRAD, and elevated TMPRSS2 is associated with immune infiltration, and the prognosis is positively correlated. In addition, tumor tissue from COVID- 19 patients with PRAD may be more susceptible to infection with SARS-COV-2, which may render the prognosis gets worse.